High Flow Nasal Cannulae in preterm infants - F. Ciuffini; M. Colnaghi; A. Lavizzari; D. Mercadante; S. Musumeci; F. Mosca (PAGEPress Publications, 2013)
Despite of improved survival of premature infants, the incidence of long term pulmonary complications, mostly associated with ventilation-induced lung injury, remains high. Non invasive ventilation (NIV) is able to reduce the adverse effects of mechanical ventilation. Although nasal continuous positive airway pressure (NCPAP) is an effective mode of NIV, traumatic nasal complications and intolerance of the nasal interface are common. Recently high flow nasal cannula (HFNC) is emerging as an efficient, better tolerated form of NIV, allowing better access to the baby's face, which may improve nursing, feeding and bonding. The aim of this review is to discuss the available evidence of effectiveness and safety of HFNC in preterm newborns with respiratory distress syndrome (RDS). It is known that distending pressure generated by HFNC increases with increasing flow rate and decreasing infant size and varies according to the amount of leaks by nose and mouth. The effects of HFNC on lung mechanics, its clinical efficacy and safety are still insufficiently investigated. In conclusion, there is a growing evidence of the feasibility of HFNC as an alternative mode of NIV. However, further larger randomized trials are required, before being able to recommend HFNC in the treatment of moderate respiratory distress of preterm infants.